(NrEWOL@CIQ (B1911-1913 (NGODOW W kITAE (B/s - (NbELOW(B, (NeWGENIJ aLEKSANDROWI^s; (NiNSTITUT KITAEWEDENIQ an sssrs ((NmOSKW(Ba :s (NiZD(B-(NWO WOSTO^NOJ LITERATURY(B,s, 1958)
(NzAKL(B.: (NS(B. 108-113s
Keywords: (NiSTORIQs